HUBUNGAN TINGKAT PERSONAL HYGIENE DENGAN STATUS INFEKSI PROTOZOA USUS PADA ANAK PANTI ASUHAN DI WILAYAH KOTA PADANG - Utami Mayfa Rahmania; Rusjdi, Selfi Renita; Lestari, Yuniar; Adrial, Adrial; Suharti, Netti; Hanum, Fathiya Juwita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
ABSTRACT Personal hygiene is how a person maintains their body's cleanliness. Orphanages, which are social welfare institutions, tend to have unstable finances and therefore have limited facilities to support personal hygiene. Poor personal hygiene practices can increase the risk of infectious diseases, such as intestinal protozoa infection. This study aims to determine the relationship between the level of personal hygiene and the status of intestinal protozoa infection in orphanage children in the Padang City.This study was an analytic study with a cross sectional design conducted at the Special Children Mentawai orphanage, Al Falah orphanage, and Syafri Moesa orphanage from October to November 2023. The results showed that most respondents (67.19%) had a poor level of personal hygiene and the incidence of intestinal protozoa infection was 39.06%. There is a significant relationship between the level of personal hygiene and the status of intestinal protozoa infection in orphanage children in the Padang City.